ANALISIS TINGKAT KELELAHAN SUBYEKTIF BERDASARKAN SIKAP KERJA PENJAHIT DI INDUSTRI KONVEKSI - Triana Izzati; Denny Ardyanto W. (Universitas Airlangga, 2018)
Work manner affects health safety and environment in the work station. It also affects workers’ fatigue which can reduce their performance resulting from the excessive of physical and mental at the working environment. The purpose of this study was to analyze the relationship between the tailor work attitude with the incidence of work fatigue on workers in the Ramli convection industry that engaged in fashion. The research was a descriptive by using the assessment of RULA model that targets of body posture of the workers in the Convection Industry. This research aimed to estimate the risk accident of skeletal muscle disorder and to assess work attitude which having pain, fatigue and musculoskeletal disorder by using RULA Model. The improvement of work attitude with changing of work position by standing up and sitting down, not slouching and not bending, and the improvement of work station such as making the ergonomic of the tailors’ chair. The results showed a strong correlation between fatigue with age (r = 0.711), work period (r = 0.854), intermediate relationship with gender (r = 0.439), work attitude (r = 0.416), and the working environment (r = 0.419). The result showed a weak correlation between fatigue with work station (r = 0.448). The conclusion is workers who have a high risk of work attitude experience a higher level of fatigue.Keywords: work attitude, work fatigue, work station